2010
DOI: 10.1002/jmv.21754
|View full text |Cite
|
Sign up to set email alerts
|

DNA of mouse mammary tumor virus‐like virus is present in human tumors influenced by hormones

Abstract: Mouse mammary tumor virus (MMTV) is a hormonally regulated, oncogenic virus of mice. MMTV-like virus DNA has previously been detected in human breast cancers, liver disease, and liver cancers. It is hypothesized that local hormonal effects might be of primary importance in determining MMTV-like virus detection in human tumors. MMTV-like virus envelope (env) DNA was determined using nested PCR in 89 ovarian, 147 prostate, 50 endometrial, 141 skin, and 51 lung cancers. Viral-positive sequences were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…EBV has been associated with Hodgkins lymphoma, Burkitts lymphoma and nasopharyngeal cancer. MMTV has been identified in human breast, prostate and liver tissues [20], [41].…”
Section: Discussionmentioning
confidence: 99%
“…EBV has been associated with Hodgkins lymphoma, Burkitts lymphoma and nasopharyngeal cancer. MMTV has been identified in human breast, prostate and liver tissues [20], [41].…”
Section: Discussionmentioning
confidence: 99%
“…It could be the explanation of the different between them [15,24]. Previous studies report on the presence of viruses in patients who have other malignancies [25]. In a previous paper, we reported on the presence of MMTV-like gene sequences in the INER51 lung cancer cell line.…”
Section: Discussionmentioning
confidence: 83%
“…We amplified the MMTV-like LTR-gag region using the primers reported by Liu et al to confirmed their positivity [18] Furthermore, we used the INER51 cell line as a positive control. In 2010, Johal H et al[25] reported on the detection of MMTV-like env sequences in ovarian, prostate, endometrial, and skin cancers, but not in lung cancer, indicating that MMTV-like presence is not restricted to breast cancer cells. We detected MMTV-like gene env sequences in the INER51 lung cancer cell line [23].…”
Section: Discussionmentioning
confidence: 99%
“…While this work was in progress, a report was published indicating that MMTV-like sequences were present in 10% of the ECs of Australian women. 11 In this communication, we show that 23.2% of the ECs tested in American women contained HMTV env gene sequences, which are 94% homologous to MMTV. We exclude the possibility of contamination with mouse sequences by careful testing for the presence of murine DNA in all experiments.…”
mentioning
confidence: 71%